Nursing Care for Ny 'S with Impaired Sense of Security and Comfort Acute Pain Associated with Physical Injury Agents Post-Section Caesarea - Rizki Dian Cahyawati; Dewi Erna Marisa; Sumarni Sumarni; Dikha Sazilli; Mahendra Mahendra (Al Makki Publisher, 2024)
The World Health Organization has determined that the average rate of sectio cesarean delivery in a country is around 5-15% per 1,000 births. Sectio cesarean delivery is the process of giving birth surgically by making incisions in the mother's abdomen (laparotomy) and uterus (hysterotomy) to remove the baby. One of the effects of SC is post-SC pain, which is caused by an incision or tear in the tissue of the front abdominal wall. Pain is an unpleasant sensory and emotional experience that results from actual and potential tissue damage, regardless of the nature, pattern, or cause of the pain. This study aims to describe the disturbance of a sense of security and comfort due to pain in post-Sectio Caesarea patients at Sumber Kasih Cirebon Hospital. This study uses a case study method by applying nursing care to the patient Mrs. for assessment, diagnosis, intervention, implementation, and evaluation. The results showed that the patient's comfort and pain disorders could be overcome, with the patient no longer complaining of pain and the pain scale reduced from 5 to 1. Thus, the patient's problem can be said to be resolved. The implications of this study indicate that appropriate nursing interventions can significantly reduce post-sectio cesarean pain, thereby improving the quality of life of postoperative patients.